18th International HLA and Immunogenetics Workshop: Report on the SNP-HLA Reference Consortium (SHLARC) component - Silva, Nayane S. B. [UNESP]; Bourguiba-Hachemi, Sonia; Douillard, Venceslas; Koskela, Satu; Degenhardt, Frauke; Clancy, Jonna; Limou, Sophie; Meyer, Diogo; Masotti, Cibele; Knorst, Stefan; Naslavsky, Michel Satya; Franke, Andre; et al. (Wiley, 2024)
The SNP-HLA Reference Consortium (SHLARC), a component of the 18th International HLA and Immunogenetics Workshop, is aimed at collecting diverse and extensive human leukocyte antigen (HLA) data to create custom reference panels and enhance HLA imputation techniques. Genome-wide association studies (GWAS) have significantly contributed to identifying genetic associations with various diseases. The HLA genomic region has emerged as the top locus in GWAS, particularly in immune-related disorders. However, the limited information provided by single nucleotide polymorphisms (SNPs), the hallmark of GWAS, poses challenges, especially in the HLA region, where strong linkage disequilibrium (LD) spans several megabases. HLA imputation techniques have been developed using statistical inference in response to these challenges. These techniques enable the prediction of HLA alleles from genotyped GWAS SNPs. Here we present the SHLARC activities, a collaborative effort to create extensive, and multi-ethnic reference panels to enhance HLA imputation accuracy.
Keywords: 18th International HLA and Immunogenetics Workshop; HLA; imputation; reference panel; SHLARC; SNP